Exploiting phosphate-starved cells of scenedesmus SP for the treatment of raw sewage - Yewalkar-Kulkarni, Swati; Gera, Gayatri; Nene, Sanjay; Pandare, Kiran; Kulkarni, Bhaskar; Kamble, Sanjay (Indian Journal of Microbiology, 2017)
Phosphate depletion is one of the favorable ways to enhance the sewage water treatment with the algae, however, detailed information is essential with respect to internal phosphate concentration and physiology of the algae. The growth rate of the phosphate-starved Scenedesmus cells was reduced drastically after 48 h. Indicating cells entered in the stationary phase of the growth cycle. Fourier Transform Infrared analysis of phosphate-starved Scenedesmus cells showed the reduction in internal phosphate concentration and an increase in carbohydrate/phosphate and carbohydrate/lipid ratio. The phosphate-starved Scenedesmus cells, with an initial cell density of, 1 x 10(6) cells mL(-1) shows 87% phosphate and 100 % nitrogen removal in 24 h. The normal Scenedesmus cells need approximately 48 h to trim down the nutrients from wastewater up to this extent. Other microalgae, Ankistrodesmus, growth pattern was not affected due to phosphate starvation. The cells of Ankistrodesmus was able to reduce 71% phosphate and 73% nitrogen within 24 h, with an initial cell density of, 1 x 10(6) cells mL(-1).
Keywords: Ankistrodesmus; Fourier Transform Infrared; Phosphate starvation; Scenedesmus; Sewage treatment

Early detection of KP.2 SARS-CoV-2 variant using wastewater-based genomic surveillance in Pune, Maharashtra, India - Rajput, Vinay; Das, Rashmita; Pramanik, Rinka; Nannaware, Kiran; Sushma, Y.; Taji, Nyabom; Rajput, Vishal; Rajkhowa, Riyakshi; Pacharne, Poonam; Shah, Priyanki; Gogate, Niharika; Sangwar, Poornima; et al. (Journal of Travel Medicine, 2024)

Enhanced degradation of ciprofloxacin hydrochloride using hybrid advanced oxidation process of hydrodynamic cavitation and ozonation - Bodawar, Narendra; Shetty, Rohit; Kamble, Sanjay; Kulkarni, Prashant (Chemical Engineering & Technology, 2024)
The degradation of ciprofloxacin hydrochloride (CFX), an extensively utilized antibiotic for bacterial infections, has been studied through the application of advanced oxidation processes (AOPs) including hydrodynamic cavitation (HC), ozonation (O3), the Fenton reaction, chemical oxidation, and hybrid AOPs such as HC/O3 and Fenton/O3. Among these, the hybrid combination of HC/O3 demonstrated the highest CFX degradation of 99.82 % within 180 min having an initial concentration of 1000 ppm. The optimization of the HC/O3 process was conducted by varying parameters including initial concentration, pH, ozone (O3) gas flowrate, and temperature. Throughout the degradation process, CFX underwent intermediate formation, which gradually degraded over time. The hydrodynamic cavitation (HC) in combination with ozone, referred to as the HC/ozonation process, was used for the degradation of ciprofloxacin hydrochloride present in wastewater. This process underwent optimization with respect to various reaction parameters, including the initial concentration, ozone flow rate, pH level, temperature, the influence of ions, and the specific water matrix. At these optimized conditions a degradation efficiency of 99.82 % was achieved after 180 min. image
Keywords: active pharmaceutical ingredients; Advance Oxidation Processes; Ciprofloxacin hydrochloride; Hybrid AOPs; Hydrodynamic cavitation